Micro, Small, and Medium Enterprises' Digital Marketing Strategy in Cimekar Village, Bandung Regency - I Nyoman Tri Sutaguna; Syamsu Rijal; Chevy Herli Sumerli A; Geofakta Razali; Muhammad Yusuf (Pusat Riset dan Inovasi Nasional, 2023)
The slow growth of Micro, Small, and Medium Enterprises in rural areas has resulted in low sales volume. Despite the fact that MSMEs provide employment opportunities for rural communities, they do not eliminate poverty or unemployment. To make the most of digital media, solid digital marketing strategies and concepts are required. Digital marketing is the use of social media networks to conduct promotional activities and map digital markets. Digital marketing ideas can bring geographically dispersed parties together by using computers or other electronic equipment. The goal of this research project is to identify the most effective digital marketing tactics for the growth of MSMEs in Cimekar village, Bandung regency. The descriptive qualitative research method was used in this study. The data for this study is gathered through observations, interviews, and secondary sources such as books, journals, and articles. According to the findings of this study, MSMEs' productivity growth in Cimekar Village has been negative. Even if a website for an online business has already been created, not everyone has implemented a digital marketing strategy. As can be seen, the digital marketing strategy has received little attention from MSMEs in Cimekar Village, Bandung Regency. So it is hoped that MSMEs in Cimekar Village, Bandung Regency, will be able to adapt to changing times by selling online using digital marketing strategies. not everyone has implemented a digital marketing strategy. As can be seen, the digital marketing strategy has received little attention from MSMEs in Cimekar Village, Bandung Regency. So it is hoped that MSMEs in Cimekar Village, Bandung Regency, will be able to adapt to changing times by selling online using digital marketing strategies. not everyone has implemented a digital marketing strategy. As can be seen, the digital marketing strategy has received little attention from MSMEs in Cimekar Village, Bandung Regency. So it is hoped that MSMEs in Cimekar Village, Bandung Regency, will be able to adapt to changing times by selling online using digital marketing strategies.